Anthropometric and physical performance attributes between positions of elite youth rugby union / Amirul Mustaqim Ahmad - Ahmad, Amirul Mustaqim (Faculty of Sport Science and Recreation, 2016)
The aims of this study is to determine the anthropometric measurement physical performance attributes on playing positions which are backlines and forwards in rugby union. The anthropometric measurement and physical performance attributes consists of Body Mass Index(BMt), body fat percentage, agility, power, and maximal aerobic power. Forty (N=40) elite youth rugby players from Sport School Tunku Mahkota Ismail (SSTMI) were recruited using random sampling technique. It is hypothesized that backlines position is greater than forwards position due to their physical performance attributes. The result showed that there were no significant differences for BMI, body fat percentage, agility and power for the backlines and forwards positions, but there was significant different on maximal aerobic power for backlines and forwards. In conclusion, maximal aerobic power shows asymmetry result. For other result, both positions showed no differences on anthropometric measurement and physical performance attributes.